Membangun Konsensus dan Mengelola Konflik Kerjasama Pemerintah-Swasta dalam Penyediaan Air Bersih - Nugroho, Hanantyo Sri (Universitas Serang Raya, 2017)
Market restructuring in the form of bureaucratic entrepreneurship enables the government to achieve the results needed to solve the problem. However, such a dominant worldview proves unsuccessful in providing problem solving. On the one hand, the emergence of a new economic relations structure in the form of public-private partnerships should continue to contribute positively to the private sector in gaining advantage over the sustainability of cooperation, whereby market mechanisms become incentives that allow private parties to derive interest from their involvement. On the other hand, government-private cooperation results in the inability of the community to access the services provided. Therefore, there is a need for a breakthrough in a more innovative contracting system so that it can become a consensus on public-private partnerships related to water supply. This research is qualitative using desk-research method. The result of the research shows that the cooperation system which is more suitable with the condition of public-private cooperation in the provision of clean water in Indonesia is the contract wake system. In the wake contracting system the water utility right is an instrument in the licensing system used by the government to limit the volume of water obtained and used by the private sector. That is, the instrument becomes the press point of government control over the use of water rights by private parties. Therefore, there is no more ownership and control over the water resources.